ACM/IEEE SC 2002 Conference (SC'02) 2002
DOI: 10.1109/sc.2002.10055
|View full text |Cite
|
Sign up to set email alerts
|

SIGMA: A Simulator Infrastructure to Guide Memory Analysis

Abstract: In this paper we present SIGMA (Simulation Infrastructure to Guide Memory Analysis), a new data collection framework and family of cache analysis tools. The SIGMA environment provides detailed cache information by gathering memory reference data using software-based instrumentation. This infrastructure can facilitate quick probing into the factors that influence the performance of an application by highlighting bottleneck scenarios including: excessive cache/TLB misses and inefficient data layouts. The tool ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 19 publications
0
35
0
Order By: Relevance
“…The compression algorithm maintains a queue of MPI events and attempts to greedily compress the first matching sequence, an approach that is loosely based on the SIGMA scheme for memory analysis [9]. Our algorithm uses two sequences, the "target" and the "match" sequence, each with its own head and tail pointer.…”
Section: Intra-node/task-level Trace Compressionmentioning
confidence: 99%
“…The compression algorithm maintains a queue of MPI events and attempts to greedily compress the first matching sequence, an approach that is loosely based on the SIGMA scheme for memory analysis [9]. Our algorithm uses two sequences, the "target" and the "match" sequence, each with its own head and tail pointer.…”
Section: Intra-node/task-level Trace Compressionmentioning
confidence: 99%
“…Constant and loop-varying addresses need to be encoded only once in the compressed trace, but all chaotic addresses must be stored separately. Control flow analysis to extract loop information can be avoided if a program is instrumented before tracing [DeRose et al 2002]. However, the limitation of this technique is that the iteration count for inner loops must be constant.…”
Section: Related Workmentioning
confidence: 99%
“…From previous studies with a variety of HPC applications [9,4,11,12,10,17], we have found that these five dimensions (CPU, memory, message passing, threads and I/O) provide an excellent starting point for a programmer to understand the performance behavior of their applications. The dimensions of performance data provided in our current framework are 1 :…”
Section: Overview Of the Productivity Cen-tered Framework For Applicamentioning
confidence: 99%